EVALUASI KEBIJAKAN PENDIDIKAN GRATIS DAN WAJIB BELAJAR 12 TAHUN DI KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Krisno Wibowo E.42009070 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2021)
This Skripsi is intended to evaluate he Implementation of Free Education Policy and Obligation of 12 Years Learning Program in Sukadana Subdistrict of Kayong Utara Regency and how the implementation of Free Education policy and obligation of 12 the years learning is moving. In this skripsi, the researcher analyse the problem by using the theory from Langbein which is evaluate the process by analysing of the technical guide and execution. In this case, the writer is using the Aid of Education Operational ( BOP) technical guide .The researcher used 2 (two) indicators of technical guide execution of BOP that are fund of BOP and Bantuan Siswa Miskin ( BSM). BOP accepted by the school is still unappropriate with RKA-KS compiled by school, so that a lot of activities and programs at the school canceled or do not run properly and facilities in some schools are still very less and concern. While BSM distribution is still less from its goal.Suggestion refering to this research result expected  for Local Government of Kayong Utara Regency is improving the socialization process to parents and society for the importance of education, adding school facilities, making new regulation arrangging about sanction for child desistion or break the school so that the obligation of 12 years learning and quality of education in Kayong Utara Regency become better. Key words: evaluation, implementation, technical guide of BOP, Bantuan Operasional Pendidikan (BOP), Bantuan Siswa Miskin (BSM), the obligation of 12 years learning